The true identity of Sedum meehanii (Crassulaceae) - Gallo, Lorenzo (Phytotaxa, 2021)
Sedum meehanii (Gray 1881: 105) was based on plants sent from a nursery in Philadelphia, said to have originated in Utah (United States) in 1874 (Clausen 1975: 68). In 1946 Clausen annotated the type collection to S. hispanicum Juslenius [sic!]. Cronquist et al. (1997) excluded S. meehanii from the Intermountain Flora, and followed Clausen in synonymizing it with S. hispanicum Linnaeus (1755: 12). Welsh (1982) and Welsh et al. (1987) tentatively placed S. meehanii as a synonym of S. lanceolatum Torr. (1827: 205), a species native species in Utah. Ohba (2009) interpreted the specimen as a naturalized adventive, not cultivated, and accepted S. hispanicum as a member of the Utah flora. ’t Hart & Bleij (2003) instead treated S. meehanii among “unresolved applications” of the genus Sedum.